2016
DOI: 10.12659/pjr.896103
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Intravasation During Hysterosalpingography

Abstract: SummaryHysterosalpingography is an imaging method to evaluate the endometrial and uterine morphology and fallopian tube patency. Contrast intravasation implies backflow of injected contrast into the adjoining vessels mostly the veins and may be related to factors altering endometrial vascularity and permeability. Radiologists and gynaecologists should be well acquainted with the technique of hysterosalpingography, its interpretation, and intravasation of contrast agents for safer procedure and to minimize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…It may be related to predisposing factors altering endometrial vascularity and permeability. Bhoil et al reported an increased risk of intravasation during HSG in women with certain clinical conditions like nonspecific pelvic pain, menometrorrhagia, secondary infertility, ectopic pregnancy, polycystic ovarian disease, endometriosis, hydatidiform mole, vaginal itching, and subclinical urinary infections. Nevertheless, it may be seen in patients with no abnormalities, as well as in those with a history of recent uterine surgery or increased intrauterine pressure due to tubal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…It may be related to predisposing factors altering endometrial vascularity and permeability. Bhoil et al reported an increased risk of intravasation during HSG in women with certain clinical conditions like nonspecific pelvic pain, menometrorrhagia, secondary infertility, ectopic pregnancy, polycystic ovarian disease, endometriosis, hydatidiform mole, vaginal itching, and subclinical urinary infections. Nevertheless, it may be seen in patients with no abnormalities, as well as in those with a history of recent uterine surgery or increased intrauterine pressure due to tubal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently mentioned are performance of the procedure during the early postmenstrual and late preovulatory periods; the presence of Mullerian duct anomalies; pelvic discomfort and unusual lingering pain during HSG; menometrorrhagia; polycystic ovary syndrome; endometriosis; uterine malformations related to secondary infertility, recurrent miscarriages, endometrial injury, complicated delivery, and Asherman's syndrome; and subclinical urinary infections. 6,7 No consensus has been reached regarding the role of high pressure in the uterine cavity during HSG. Our hypothesis assumes that a main cause of the green urine sign following intravasation is the short-lasting increase in pressure in the uterine cavity during chromopertubation.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently mentioned are performance of the procedure during the early postmenstrual and late preovulatory periods; the presence of Mullerian duct anomalies; pelvic discomfort and unusual lingering pain during HSG; menometrorrhagia; polycystic ovary syndrome; endometriosis; uterine malformations related to secondary infertility, recurrent miscarriages, endometrial injury, complicated delivery, and Asherman’s syndrome; and subclinical urinary infections. 6 , 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations